Електрична система тестування з теоретичної електротехніки - Толмачов, Станіслав Трохимович; Ільченко, Олександр Володимирович (НТУ "ХПІ", 2007)
Обговорюються деякі питання змісту дисципліни "Теоретичні основи електротехніки" та шляхи підвищення якості навчання. Розглянуті особливості навчальної програми "Електронний практикум з TOE", яка може бути використана як універсальний засіб комп’ютерного тестування студентів з метою активізації їх самостійної роботи. Програма розроблена на кафедрі електромеханіки Криворізького технічного університету. Реалізовані україно- та російсько-мовна версії програми в локальному та мережевому варіантах.

Some questions of the content of "Theoretical Electrical Engineering" discipline and ways of education quality improvement are discussed. Features of educational program "Electronic practicum for theoretical basis of electrical engineering" are considered. The program can be used as a universal facility for computer-aided testing of students with the purpose of their independent work activation. The program is developed in Electromechanical Engineering Department of Kriviy Rih Technical University. A Ukrainian- and a Russian-language program versions in local and network variants are realized.
A computer-based testing system for "Theoretical Electrical Engineering" discipline
Keywords: електротехніка; електромеханіка; підготовка фахівців; навчальні програми; theoretical electrical engineering; teaching quality; electronic practical work; computer-aided testing